Subcritical Water as a Pre-Treatment of Mixed Microbial Biomass for the Extraction of Polyhydroxyalkanoates - Meneses, Liane (2022)
Polyhydroxyalkanoate (PHA) recovery from microbial cells relies on either solvent extraction (usually using halogenated solvents) and/or digestion of the non-PHA cell mass (NPCM) by the action of chemicals (e.g., hypochlorite) that raise environmental and health hazards. A greener alternative for PHA recovery, subcritical water (SBW), was evaluated as a method for the dissolution of the NPCM of a mixed microbial culture (MMC) biomass. A temperature of 150 degrees C was found as a compromise to reach NPCM solubilization while mostly preventing the degradation of the biopolymer during the procedure. Such conditions yielded a polymer with a purity of 77%. PHA purity was further improved by combining the SBW treatment with hypochlorite digestion, in which a significantly lower hypochlorite concentration (0.1%, v/v) was sufficient to achieve an overall polymer purity of 80%. During the procedure, the biopolymer suffered some depolymerization, as evidenced by the lower molecular weight (M-w) and higher polydispersity of the extracted samples. Although such changes in the biopolymer's molecular mass distribution impact its mechanical properties, impairing its utilization in most conventional plastic uses, the obtained PHA can find use in several applications, for example as additives or for the preparation of graft or block co-polymers, in which low-M-w oligomers are sought.